231k views
0 votes
3x+2y=4 x=y+3
System of equations

User Sangwook
by
5.2k points

2 Answers

5 votes
(2,-1) hope this helps :\\\
User Sang Nguyen
by
5.7k points
6 votes

Answer:

(2,-1)

Explanation:

Given system of equations:

  • 3x + 2y = 4
  • x = y + 3

We are going to use the substitution method.

Step 1: Solve for x = y + 3 for x:
(Substitute y + 3 for x in 3x + 2y = 4)

3x+2y=4

3(y+3)+2y=4

5y + 9 = 4 ----> Simplify both sides of the equation

5y+9+−9=4+−9 -------> Add -9 to both sides

5y=−5

5y5 = -5/5 ------> Divide both sides by 5

y = −1

Step 1: Substitute -1 for y in x = y + 3:

x = y + 3

x = -1 + 3

x = 2 --------> (Simplify both sides of the equation)

Answer:

(2,-1)

User Aravind Sivam
by
5.2k points